2017
DOI: 10.1111/ojoa.12102
|View full text |Cite
|
Sign up to set email alerts
|

The Mesolithic–Neolithic Transition in the Channel Islands: Maritime and Terrestrial Perspectives

Abstract: Summary. This paper investigates the Mesolithic-Neolithic transition in the Channel Islands. It presents a new synthesis of all known evidence from the islands c.5000-4300 BC, including several new excavations as well as find-spot sites that have not previously been collated. It also summarizes -in English -a large body of contemporary material from north-west France. The paper presents a new high-resolution sea-level model for the region, shedding light on the formation of the Channel Islands from 9000-4000 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Although this trend is widely accepted as a global phenomenon, the Neolithic period did not have uniform moments of introduction and development. For the geographical areas concerned in this study, it is worth recapping that whilst the Neolithic 'package' is recognized in Iberia from at least the 6 th millennium cal BC (Bernabeu-Auban and Pardo-Gordo 2017; Martins et al 2015), reaching its NW 1000 years later, and identified in NW France (Brittany) around 5200 BC, it only arrives to the British Isles in 4050 cal BC (Garrow and Sturt 2017;Whittle et al 2011). This discrepancy has important cultural implications, considering that Britain would be receiving its first strand of Neolithisation at the time that Brittany's Early…”
Section: Atlantic Rock Art Connectedmentioning
confidence: 94%
See 2 more Smart Citations
“…Although this trend is widely accepted as a global phenomenon, the Neolithic period did not have uniform moments of introduction and development. For the geographical areas concerned in this study, it is worth recapping that whilst the Neolithic 'package' is recognized in Iberia from at least the 6 th millennium cal BC (Bernabeu-Auban and Pardo-Gordo 2017; Martins et al 2015), reaching its NW 1000 years later, and identified in NW France (Brittany) around 5200 BC, it only arrives to the British Isles in 4050 cal BC (Garrow and Sturt 2017;Whittle et al 2011). This discrepancy has important cultural implications, considering that Britain would be receiving its first strand of Neolithisation at the time that Brittany's Early…”
Section: Atlantic Rock Art Connectedmentioning
confidence: 94%
“…Distributional analysis of the alpine axes demonstrated their wide spread including into core areas of this study (Fábregas-Valcarce et al 2015;Pétrequin et al 2008;Pétrequin et al , 2015. We also see polished axes, stone rings and beads, arrowheads, halberds, some daggers and jewellery circulating from the 4 th millennium BC, alongside pottery making traditions, whose forms are imitated elsewhere (Anderson-Whymark and Garrow 2015:67;:1122Garrow and Sturt 2017;Peña-Santos 2003: 70-72;Rodríguez-Rellán et al 2015:137-138). Ceramics are one of the main traits of the Neolithic and are extensively used to characterize strands of Neolithisation and prehistoric movement (e.g.…”
Section: The Materials Culturementioning
confidence: 97%
See 1 more Smart Citation
“…Would this have been perceptible to individuals and communities and in oral tradition? There is lithic ( 16 , 21 ) and palynological evidence ( 22 , 23 ) for seasonal occupation on Scilly during the Late Mesolithic, with more persistent settlement during the Middle Neolithic suggested from land clearance, ceramics, and agricultural practice ( 22 , 23 ). During these periods, the average loss in land area reduced from ~15.5 km 2 per millennium in the Early Holocene to ~12.5 km 2 per millennium during the Mid-Holocene.…”
Section: Resultsmentioning
confidence: 99%
“…The migration of coastal communities displaced by this sea-level rise is a possible cause for the spread of the Neolithic transition throughout Europe ( 13 , 15 ). Rising sea levels may also have offered new opportunities for migration across northwest Europe via the expanding seaways ( 16 , 17 ). As well as opportunities, however, rising sea levels pose a range of threats (flooding, coastal erosion, land loss, habitat, and resource loss) to coastal communities.…”
Section: Introductionmentioning
confidence: 99%